AUTOSOMAL RECESSIVE POLYCYSTIC KIDNEY DISEASE - Anja Fon Gabršček; Rina Rus (The Society for Children with Metabolic Disorders, 2022)
Autosomal recessive polycystic kidney disease (ARPKD) is an inherited ciliopathy caused by mutations in the PKHD1 gene, which encodes the membrane protein fibrocystin/polyductin. Mutations lead to primary cilia dysfunction, which predominantly affects the kidneys and hepatobiliary system. The spectrum of clinical manifestations depends on the age at presentation and the predominance of renal or hepatic involvement. There is no specific treatment, hence treatment is symptomatic. Patients with end-stage kidney failure need chronic renal replacement therapy.